Different types of nationally determined contributions to address climate change - Mariana Conte Grand (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
This short article addresses four issues. First, it summarizes transparency provisions discussed in the latest Conferences of the Parties (COP19 to COP21) of the United Nations Framework Convention on Climate Change (UNFCCC). From that recompilation, it is possible to conclude that the UNFCCC moves towards the establishment of stricter transparency requirements for national climate policies. The second topic is a description of the main greenhouse gases reduction metrics, the information needed to make them equivalent, and a summary of advantages and limitations that may determine the choice of a given GHG target form over another. The third issue is a description of the facts. This is, what percentage of world's countries chose each type of target and what were the national characteristics that seem to have an impact on targets' metric choice. Finally, a difference is established between transparency and uncertainty characteristics of each nationally determined contribution form.
Keywords: 330; Klimawandel; Treibhausgas-Emissionen; Transparenz; Internationale Klimapolitik